The Role of Lifestyle Modification in The Prevention of Chronic Non-Communicable Diseases in The Adult Population (International journal of medical sciences, 2026)
The article is dedicated to the analysis of lifestyle modification as a preventive strategy against chronic non-communicable diseases in the adult population. The relevance of the study is determined by the persistent global growth of metabolic, cardiovascular, and neurodegenerative disorders that remain insufficiently controlled by pharmacological approaches alone. The novelty of the work lies in the integrative interpretation of lifestyle factors as biologically active signals capable of reshaping intracellular regulatory systems rather than as auxiliary behavioral recommendations. Lifestyle-related behaviors are conceptualized not as external modifiers but as endogenous biological inputs that dynamically regulate intracellular signaling hierarchies and inter-organ communication. The work describes the molecular and systemic mechanisms through which physical activity, dietary modulation, temporal organization of behavior, and stress-regulatory practices influence cellular energy metabolism, inflammatory control, proteostatic maintenance, and epigenetic regulation. Special attention is paid to mitochondrial dynamics, mitohormetic signaling, autophagy–lysosomal flux, neuroimmune reflexes mediated by the vagus nerve, circadian synchronization, and reversible epigenetic modifications. The article sets itself the goal of identifying convergent intracellular pathways through which lifestyle inputs translate into increased metabolic resilience and reduced disease risk. Analytical, comparative, and integrative approaches are applied to synthesize findings across molecular biology, physiology, and systems medicine. The analysis emphasizes dose-dependence, temporal specificity, and reversibility of lifestyle-induced adaptations, highlighting critical thresholds beyond which preventive efficacy is attenuated. The conclusion demonstrates that lifestyle modification operates as a coordinated regulatory intervention capable of destabilizing maladaptive metabolic states and restoring adaptive plasticity. The article will be useful for researchers, clinicians, and specialists working in preventive medicine, metabolic health, and translational physiology.